Tolerance of intonation deviation in melodic intervals in listeners of different musical training - FYK, Janina (Archives of Acoustics, 1982)
The aim of the present experimental paper was to investigate the tolerance of intonation deviations in musical intervals, depending on listeners' musical training. The investigations covered the perception of intonation deviations of chosen melodic intervals in isolation and in melodic context. Tests were edited from music material recorded on magnetic tape and were exposed by a loudspeaker to groups of 8-12 persons. The results obtained confirmed a dominating effect of musical training on the tolerance of intonation deviations in isolated intervals and those in melodic context. It was found out that in a musically trained group the tolerance of intonation deviations in intervals in melodic context was influenced by functional tendency and by the direction of intervals in a musically untrained group.